Breast Milk Jaundice - Irina A. Belyaeva; Elena P. Bombardirova; Elena O. Kurnatovskaya (Вопросы современной педиатрии)
The results of modern studies on breast milk jaundice pathogenesis, that is common form of neonatal jaundice, are presented. The major risk factors and diagnostic methods (excluding other forms of jaundice syndrome at recurrent and lingering jaundice in newborns) were defined. The main therapy approaches for breast milk jaundice were presented. Issues of phototherapy indications were discussed. The feasibility of maintaining breastfeeding in case of breast milk jaundice development was proved. This condition requires the attention of pediatricians despite the relatively favorable course and outcomes. The need to continue studies on pathogenetic therapy of such patients was noted.